Review and prospect of metacognitive therapy and metacognitive training - Dai Wenwu; Li Zhaolan; Jia Ning (Sichuan jingshen weisheng, 2022)
ObjectiveTo analyze the current research status， research hotspots and main features of the literature related to metacognitive therapy and metacognitive training， and to explore the similarities and differences in research approaches of the two intervention techniques and their research directions in the future.MethodsCitespace-based visualization analysis was carried out on the relevant literature of "metacognitive therapy" and "metacognitive training" published in 2011-2020 in the Web of Science database.Results① Adrian Wells was the core author and the author of highly cited papers in the research field of metacognitive therapy. Steffen Moritz is the core author and the author of highly cited papers in the research field of metacognitive training. Aaron T Beck was a highly cited researcher in both fields. ② The analysis of research hotspots showed that the two intervention techniques were mainly reflected in the "maturity and expansion of techniques"， "the evaluation and testing of the effects of techniques" and "the comparative analysis of techniques". ③ The key literature characteristics analysis showed that both techniques involved the aspects of "effectiveness"， "validity"， "meta-analysis" and "variation".ConclusionBoth metacognitive therapy and metacognitive training studies in 2011-2020 highlight their respective core researchers， with similarities and distinctive features in terms of research hotspots and key literature features.